Intraluminal gastrointestinal stromal tumor leading to intussusception in an adult - Parashar, Neha; Kaur, Navpreet; Tomar, Reena; Khurana, Nita; Singh, CB (Indian Journal of Case Reports, 2024)
Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the abdomen. Most of these tumors occur in the stomach. They arise from the interstitial cells of Cajal. GIST usually occurs in adults of more than 50 years of age, with a median age of 62–63 years. Fewer than 10% of cases occur at